PENGARUH FAKTOR INDIVIDU DAN DILUAR INDIVIDU TERHADAP PERILAKU ETIS MAHASISWA AKUNTANSI - Bambang Widarno, FX. Tegar Apriono, Rispantyo & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This study aims to analyze the influence of individual factors (emotional intelligence, spiritual intelligence, locus of control, equity of sensitivity) and factors outside the individual (ethical culture of the organization) on the ethical behavior of accounting students in the Faculty of Economics Slamet Riyadi University Surakarta. This research is a survey with a population of students of Faculty of Economics Slamet Riyadi University Surakarta Accounting Study Program force 2012 - 2016 with sampling technique using purposive sampling method that is the type of sample selection is not random and the number of samples of 46 students. Data collection techniques using questionnaires. Data analysis using multiple linear regression. Validity and reliability test results revealed that the valid and reliable questionnaires and darin test of classical assumption obtained the result that free data multicollinearity, free autocorrelation, no heterokedastisity and normal distributed data. Individual factors and factors outside the individual significant effect tehadap ethical behavior of accounting students with positive signified regression coefficient.Keywords: emotional intelligence, spiritual intelligence, locus of control, equity of sensitivity, organizational ethical culture